2016
DOI: 10.1002/pssa.201532909
|View full text |Cite
|
Sign up to set email alerts
|

Effect of air on oxygen p‐doped graphene on SiO2

Abstract: Stability in ambient air or in vacuum‐controlled atmosphere of molecular oxygen‐induced p‐type doping of graphene monolayer on SiO2 substrate on Si is investigated by micro‐Raman spectroscopy and atomic force microscopy (AFM). The Raman 2D and G bands spectral positions and amplitude ratio are affected by the permanence in air atmosphere in a time scale of months whereas the vacuum safely maintains the doping effects determined through Raman bands. No morphological effects are induced by the doping and post‐do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 19 publications
5
22
0
Order By: Relevance
“…Overall the effectiveness of doping by oxygen for the sample Gr/SiO 2 /Si has been proven by the previous experiments and this effect has been disentangled from the strain effect. Nevertheless, by maintaining a doped sample in ambient atmosphere for a prolonged time it is observed that some changes in the Raman spectra occur . As shown in Figure , it is found, in particular, that maintaining a sample in room atmosphere for 1 month after being treated in oxygen a red shift of the G and 2D bands peak position occurs and their intensity ratio I 2 D /I G starting from about 1, after treatment, has the tendency to go back to the native value larger than 2 suggesting that some effects have occurred to change the doping.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Overall the effectiveness of doping by oxygen for the sample Gr/SiO 2 /Si has been proven by the previous experiments and this effect has been disentangled from the strain effect. Nevertheless, by maintaining a doped sample in ambient atmosphere for a prolonged time it is observed that some changes in the Raman spectra occur . As shown in Figure , it is found, in particular, that maintaining a sample in room atmosphere for 1 month after being treated in oxygen a red shift of the G and 2D bands peak position occurs and their intensity ratio I 2 D /I G starting from about 1, after treatment, has the tendency to go back to the native value larger than 2 suggesting that some effects have occurred to change the doping.…”
Section: Resultsmentioning
confidence: 92%
“…As reported in refs. , these effects can also give rise to a complete recovery of the native sample features after a prolonged time of exposure to air and it has been suggested that the role of water in removing the doping is critical. Furthermore, the evolution of the sample during the loss of doping is featured by two trends with very different time‐scales, very similar (in opposite direction) to the already shown doping occurrence of Figure c.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations